Successful Radiosurgical Treatment of Arteriovenous Malformation Accompanied by Venous Malformation - Kurita, Hiroki; Sasaki, Tomio; Tago, Masao; Kaneko, Yuu; Kirino, Takaaki (American Journal of Neuroradiology, 1999)
Summary: We present a patient with a rare cerebrovascular malformation consisting of a typical arteriovenous malformation (AVM) with a nidus and a venous malformation (VM) in a single lesion. The AVM component was successfully obliterated by radiosurgery, whereas the VM was completely preserved. Radiosurgery can be an effective treatment technique for treating this type of malformation because it allows targeted obliteration of the AVM yet carries a low risk of damaging the venous drainage toward and away from the VM.